2011
DOI: 10.1159/000320773
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Fibrosis and Basic-Fibroblast Growth Factor-Positive Neutrophils Correlate with Colonic Stenosis in Cases of Ulcerative Colitis

Abstract: Background and Aims: The frequency of benign stenosis in ulcerative colitis (UC) is low, reported as being 3.2–11.2%, with fibrosis in the submucosa or deeper pointed out as one of the causes. The aim of the present study was to assess stenosis in UC cases using immunostaining and to analyze differences between stenotic and nonstenotic cases, focusing on basic-fibroblast growth factor (b-FGF) expression and myofibroblasts. Methods: Totals of 9 stenotic and 17 nonstenotic UC cases were histopathologically exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 34 publications
0
42
3
Order By: Relevance
“…For a long time, it was assumed that UC-related strictures were caused by muscular hypertrophy and thickening of the muscularis mucosae and muscularis propria rather than from fibrosis. However, recent studies have suggested that the cause of colonic stenosis in longstanding UC is fibrosis, possibly induced by inflammatory neutrophils producing b-FGF [25].…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, it was assumed that UC-related strictures were caused by muscular hypertrophy and thickening of the muscularis mucosae and muscularis propria rather than from fibrosis. However, recent studies have suggested that the cause of colonic stenosis in longstanding UC is fibrosis, possibly induced by inflammatory neutrophils producing b-FGF [25].…”
Section: Discussionmentioning
confidence: 99%
“…They also confirmed the overexpression of bFGF in the epithelium of patients with colitis (23). Yamagata et al reported the variability of concentration of bFGF in a single patient with colitic cancer and showed a higher bFGF-positive cell count in stenotic sites than that in non-stenotic sites (25). These reports imply that bFGF and its pathway play key roles in activated inflammation induced by immune dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Colorectal strictures may occur in both Crohn's disease (CD) and ulcerative colitis (UC) (3,4,5). Old referral centers studies, most of them published before the 90's, reported a prevalence of colonic stricture in UC ranging from 1.5% to 11% (6,7,8,9,10,11) and from 10 to 14% in CD (12,13). The occurrence of colonic strictures raises concerns about the risk of dysplasia/cancer in IBD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of the study population are listed in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12] years in UC and 8 [3][4][5][6][7][8][9][10][11][12][13][14] years in CD.…”
Section: Study Populationmentioning
confidence: 99%